Polymorphism of Dehydrocholesterol Reductase (DHCR7) Gene and its Effects on Metabolic Components of Polycystic Ovary Syndrome in Women: A Cross-sectional Study from Tertiary Care Hospital of Eastern India - Susmita Banerjee; Shuvankar Mukherjee; Anindya Dasgupta; Palash Kusum Ghosh (Journal of Clinical and Diagnostic Research)
Introduction: Polycystic Ovary Syndrome (PCOS) is a disorder characterised by various metabolic derangements with multiple origins, one of which may be linked to vitamin D metabolism. Vitamin D deficiency in individuals with PCOS not only leads to reduced bone mineralisation but also exacerbates the various symptoms associated with the condition. The role of gene variants involved in vitamin D metabolism in PCOS suggests an association with metabolic and endocrine parameters in the general population. Aim: To investigate the association of the DHCR7 gene with metabolic and endocrine parameters, including 25 Hydroxy Vitamin D {25(OH)D} levels, in women with PCOS. Materials and Methods: This was a cross-sectional study conducted in the Department of Biochemistry, Calcutta National Medical College, Kolkata, West Bengal, India, from January 2018 to February 2020. A total of 128 women with PCOS and age-matched healthy controls were enrolled. All participants were aged between 16 and 45 years. Anthropometric, metabolic, and endocrine tests were performed on both the control (n=50) and PCOS groups (case group, n=78). Polymerase Chain Reaction (PCR) with suitable primers, followed by restriction digestion using Taq1 enzyme, was used to identify Dehydrocholesterol Reductase (DHCR7) gene polymorphism in women with PCOS in Eastern India. Observations were documented regarding the associations with PCOS susceptibility. The data evaluation was conducted using Statiscal Package sfor Social Sciences (SPSS) version 20.0. A p-value<0.05 was considered statistically significant. Results: The mean age was 26.73±7.4 years for PCOS subjects and 27.68±9.2 years for healthy controls. The genotypic frequency between the two groups did not differ significantly (p-value=0.165). However, there were significant differences in Fasting Blood Sugar (FBS) with a p-value of 0.029 and Waist-hip Ratio (WHR) with a p-value of 0.05 among the individual genotypes. The lipid profile and endocrine parameters did not differ significantly between the individual genotypes. Conclusion: No statistically significant association was found between DHCR7 polymorphism and 25-hydroxy vitamin D (25-OHD) levels, as well as other metabolic parameters. However, it was observed that the susceptibility of individual genotypes in women with PCOS to alterations in certain parameters was directly related to the aggravation of symptoms and the risk of Metabolic Syndrome (MetS).